Comparison of gender determination from dental pulp and dentin after exposure to various environmental conditions: A polymerase chain reaction-based SRY gene study - Ruheena Khan; M. L. Avinash Tejasvi; Geetha Paramkusam (Wolters Kluwer Medknow Publications, 2019)
Purpose: Sex determination becomes the first priority by a forensic investigator in the process of identification of bodies mutilated beyond recognition due to mass disasters. Sex-determining region Y (SRY) gene is used as a sex-typing marker as the results are said to be 100% accurate. Therefore, an experimental study was conducted to rule out the possibility of the presence of SRY gene in tooth pulp and dentin after being exposed to various environments. Materials and Methods: Twenty extracted teeth of known gender were taken, of which ten were male and ten were female. The tooth samples were subjected to various environmental conditions for 60 days. Results: Among the total twenty samples, DNA isolation was done from all the samples of pulp and dentin. Gender determination using SRY gene was correct in all the samples of the pulp, and no interpretation of SRY was possible from the dentin though the DNA was isolated. Conclusion: The present study has found DNA retrieval can be done from human teeth irrespective of the storage time and environmental conditions for forensic caseworks and SRY gene to be a reliable biomarker for sex determination from the pulp tissue of teeth.